Overview of Environmental Sanitation and Socio-Cultural of Coastal Communities in Fishing Village, Medan Belawan District, Indonesia - Nasution, Amalia Rahmi; Romiza Arika; Cut Nasywa Kesuma Dany; Mawaddah Sri Rezeki Dalimunthe; Desri Amrainum; Ella Asri Fauziah; Fatma Salsabila; Indah Rizqika; Mayumi Ershanda; Muhammad Subhan (HM Publisher, 2023)
An overview of environmental and socio-cultural sanitation is very interesting to explore. Environmental sanitation and the social culture of coastal communities in fishing villages are inseparable aspects of their daily lives. This study aimed to understand the description of environmental sanitation and socio-culture of the coastal community of fishing village, Medan Belawan District, Indonesia, in order to create sustainable and equitable solutions for them. This study is a descriptive observational study. A total of 100 informants were included in this study. Data analysis was carried out univariately to present environmental sanitation and socio-cultural data. Waste processing in the environment is still very bad, where garbage is generally just piled up, and no waste management efforts are carried out. The community also does not have healthy latrines, which shows that sanitation conditions are still not a good report. The majority report also does not have refrigerators as food storage, and the community, in general, has not implemented a clean and healthy lifestyle. The source of clean water and processed drinking water treatment also still show things that are not good. Water sources and processing that are not optimal make the majority of people experience skin problems. The overview of environmental sanitation and the socio-culture of coastal communities in fishing villages shows how important it is to increase efforts to keep the environment clean and maintain cultural values in their daily lives.